RELATIONS, INTERACTIONS AND NETWORKS OF CULTURAL TOURISM STAKEHOLDERS IN RURAL AREAS OF VOJVODINA - Pavlović, Nataša; Medić, Sandra; Tešić, Aleksandra (Economics of Agriculture, 2015)
Contemporary trends, which are characterized by a very strong level of competition and the maturity of the market, become more than ever essential for success of tourist destinations. Rural areas in Vojvodina, because of its authentic atmosphere and multiculturalism, have signifcant advantages for cultural tourism. Each participant who creates a tourism product in todays competitive environment aims to have a strong focus on customer satisfaction, which indicates the necessity of adopting the concept of total relationship marketing. The aim of this paper is to show how cultural institutions, souvenir craftsmen, tourism organizations, travel agencies and other stakeholders achieve cooperation and apply modern concept of total relationship marketing for the purposes of satisfying the needs of tourists. The paper will explore the fundamental postulates of relationship marketing applied by key stakeholders of cultural tourism in rural areas, and will get reference results on relations, interactions and networks.